Assessing the effects of learning style in business statistics. (1st January 2013) - Stevens, David P.
Business majors at AACSB accredited schools are required to take undergraduate statistics. Much research has been done with various learning style models for students enrolled in core business courses such as accounting, management, economics, and finance. However, the author has found no research that attempts to quantify the effects of learning style for students in business statistics. This study demonstrates that learning style as measured using the VARK model has significant effects on numerous variables of interest including academic success, student perceptions of course and instructor and academic major. The effect sizes are standardised and may be compared across studies. These findings provide a rationale for the delivery of course content in various modes to optimise student experiences and success.